Investor Trust in Securities Depository Institutions: A Phenomenological Literature Review in Emerging Capital Markets - Budi Mawan Aris; Husnaeda; Irpan; Muchriana Muchran; A. Ifayani Haanurat (Pustaka Digital Indonesia, 2026)
This study aims to systematically examine and synthesize existing literature on investor trust in depository institutions within capital markets. Employing a qualitative literature review approach, this research integrates findings from prior empirical and conceptual studies to identify key determinants, theoretical perspectives, and emerging patterns related to trust formation. The analysis focuses on how investors perceive the role of depository institutions in ensuring the security, transparency, and reliability of securities ownership and transaction settlement systems. The results indicate that investor trust is primarily shaped by service quality, institutional reputation, system reliability, information transparency, and regulatory support. In particular, technological stability, secure electronic depository systems, and timely settlement processes significantly enhance investor confidence. Furthermore, trust is conceptualized as a multidimensional construct encompassing perceived security, legal certainty, and confidence in institutional integrity and professionalism. The findings also highlight that positive user experience and consistent system performance strengthen long-term trust, while system failures and lack of transparency may erode investor confidence. This study underscores the strategic role of depository institutions as a critical infrastructure in maintaining market integrity and fostering investor participation. By consolidating fragmented literature, this review contributes to the development of a comprehensive understanding of trust in capital market institutions and provides implications for policymakers and practitioners in improving service quality, regulatory frameworks, and technological resilience to sustain investor trust and market stability.